Bagimu Dīnmu Bagiku Dīnku: Jejak-jejak Falsafah dan Sosial-Budaya Ayat al-Kāfirūn [109]: 6 - Nanang Tahqiq (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2006)
At least three approaches deserve significant attention. First, by tracing the teachings of Islam from its founder, Prophet Muhammad. Second, paying attention to historical Islam, towards the civilizations built by Muslim communities in various parts of the world, in the context of history after the Prophet. And third, by claiming that “Prophetic Islam” and “historical Islam” are not appealing, focusing on whatever actions Muslims are currently taking here. Contemporaneity, therefore, is more dominant and considered more attractive in this latter approach. However, this article seeks to leave behind the complexities brought about by these paradigmatic debates. This article emerges with the intention of addressing the ongoing issues faced by the Indonesian Muslim community, to then be discussed and solutions sought within the broader framework of “religious freedom.” Thus, this article avoids being faithful to any one of the three paradigms mentioned, but rather uses all three as references and foundations for our research.